A New Technique for Estimating the Lifetime of Bursts of Electron Precipitation From Sounding Rocket Measurements. Issue 18 (25th September 2020) - Hecht, J. H.; Clemmons, J. H.; Lessard, M. R.; Kenward, D. L.; Sadler, F. B.; Fritz, B. A.; Evans, J. S.; Lynch, K. A.
Abstract: At 0735 UT on 13 December 2015, the Rocket Experiment for Neutral Upwelling‐2 experiment launched north toward the auroral cusp region from Andoya, Norway. The instrumented rocket included an electron spectrometer, photometers that measured the auroral redline and greenline, and an instrument that measured ionospheric thermal electron temperature. On the down leg, just south of Svalbard, the rocket entered a region of poleward moving auroral forms that were characterized by narrow structures due to a combination of spatial and temporal variations. A noticeable feature was that the redline to greenline brightness ratio was much smaller than expected. A model is developed that shows that these emissions can be used to estimate the lifetimes of bursty electron precipitation. This model is shown to be consistent with some poleward moving auroral form lifetimes being on the order of 100 ms. The correlation between the precipitation and temperature bursts suggest that some transport occurred. Key Points: A new optical technique has been developed for measuring the lifetime of electron precipitation events from sounding rockets This technique was applied to RENU2 flight data, and it was estimated that some ofthe observed PMAFs had lifetimes on the order of 100 ms